Um estudo de consenso Delphi para estabelecer o conjunto mínimo de informações essenciais para registro nos programas de reabilitação pulmonar no Brasil - Pereira, André Gonçalves (Universidade Federal de São Carlos, 2025)
Chronic respiratory diseases (CRD), such as Chronic Obstructive Pulmonary Disease (COPD) and asthma, represent a significant challenge for global public health, with particularly severe social and economic impacts in low- and middle-income countries. These chronic conditions increase the demand for health care and reduce the quality of life of patients. Pulmonary rehabilitation (PR) is widely recommended as an effective non-pharmacological intervention for the management of CRD, providing benefits in functional capacity and quality of life. However, the lack of standardization of the information collected in these programs makes it difficult to analyze the results and develop effective policies for the health sector. Objective: To establish a minimum set of essential information for recording in pulmonary rehabilitation programs in Brazil, aiming to support science and planning of public health actions, allowing these data to be used as consistent indicators for health management. Methodology: This is an observational study conducted using the Delphi method. Two expert panels, composed of researchers, health professionals and patients with CRD, participated in the study. The initial questionnaire was developed based on international initiatives and guidelines and aimed to obtain consensus on 13 items to be collected at different moments of pulmonary rehabilitation: admission, discharge and follow-up. After its construction, the questionnaire was distributed through non-probabilistic sampling, using the snowball method. The items were scored on a 9-point Likert scale. Items with a consensus score higher than 70% were included in the final set. Items considered essential by only one of the groups of participants or that presented low agreement (rejection equal to or higher than 15% of the participants) were rewritten by the researchers and submitted to a second round of consultation. If they did not reach consensus after this stage, the items were excluded. The survey was conducted in two rounds, the first between June 8, 2024 and August 23, 2024, while the second was conducted between September 17, 2024 and October 24, 2024. Results: A total of 47 participants from the five regions of Brazil completed the first round of the survey, including 31 health professionals, 9 researchers and 7 individuals with CKD. The average age of professionals and researchers was 37.7 years, while participants with CKD had an average age of 56.4 years. The training of health professionals was predominantly physiotherapists (97.5%), and the majority of participants were female (72.5% and 85.7%, respectively). In the second round, there was a retention rate of 70%, with the participation of 33 individuals: 30 health professionals and researchers and 3 participants with CKD. After final data analysis, consensus was reached on essential items for PR, organized at the time of admission, discharge, and follow-up. The defined items include sociodemographic information, lung health, risk factors, comorbidities, disease impact, dyspnea assessment, functional capacity, strength, endurance, functional limitations, program details, number of exacerbations, economic impact, and psychological status. Conclusion: This study defined a minimum set of essential data for registration in Pulmonary Rehabilitation Programs in Brazil. This set aims to standardize data, facilitate comparisons between programs, identify best practices, and improve the quality of services. In addition, future research should refine metrics and evaluate their practical adoption, promoting sustainable implementation in PR programs.
A Delphi consensus study to establish the minimum set of essential information for registration in pulmonary rehabilitation programs in Brazil
Keywords: Doenças Respiratórias; Reabilitação pulmonar; Países em desenvolvimento; Brasil; Informações em saúde; Auditoria; Respiratory Diseases; Pulmonary Rehabilitation; Developing Countries; Brazil; Health Information; Audit; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL